Connection Between Track Geometry Quality and Dynamic Vehicle Response at Various Speeds - Csaba Ágh (The Baltic Journal of Road and Bridge Engineering)
Track geometry measurements are widely used for describing track quality. However, derailments and track deterioration are caused by forces arising in vehicle-track system. This research focuses on two types of vehicle response. Firstly, the influence of the longitudinal level irregularities on the vertical wheel-rail forces was examined. Secondly, the correlation between the lateral axle box acceleration and the cross level irregularities was investigated. Track geometry and vehicle response data were acquired simultaneously by a track recording car, formed from a passenger car, at various speeds up to 130 km/h. Vehicle-track forces were calculated based on accelerometers mounted on the car body, bogies and axle boxes, considering mass and moment of inertia. Non-linear regressions resulted in vertical vehicle-track force estimation functions. It was proven that the use of second spatial derivatives of the longitudinal level gave a better estimation than the use of reference TQIs according to European Standard EN 13848-6. A linear relationship was found between the speed and standard deviation of vertical vehicle-track forces. On straight sections with constant speed, correlation coefficients of around 0.8 were found between second spatial derivatives of cross level and lateral axle box acceleration.